2015
DOI: 10.1002/jcla.21846
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐A, HLA‐B, and HLA‐DRB1 Allele and Haplotype Frequencies in Renal Transplant Candidates in a Population in Southern Brazil

Abstract: This study provides the first data on the HLA-A, HLA-B, and HLA-DRB1 allele, phenotype and haplotype frequencies of renal transplant candidates in a population in southern Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
3
0
3
Order By: Relevance
“…Полученные нами данные созвучны с результатами исследования, проведенными в Бразилии, где среди пациентов с ХБП также наиболее часто выявлялся HLA-А02 (25,4%) (у нас данный АГ выявлялся наиболее часто) и другие антигены -HLA-В44 (10,9%) и HLA-DR13 (13,9%) [45]. В другом исследовании из этой же страны у кандидатов на трансплантацию почки наиболее часто выявлялись HLA-А02, HLA-B35 и HLA-DR11, что также созвучно с нашими результатами (у нас данные АГ выявлялись в 53,7%, 19,75% и 16,05% случаев соответственно) [44].…”
Section: Discussionunclassified
“…Полученные нами данные созвучны с результатами исследования, проведенными в Бразилии, где среди пациентов с ХБП также наиболее часто выявлялся HLA-А02 (25,4%) (у нас данный АГ выявлялся наиболее часто) и другие антигены -HLA-В44 (10,9%) и HLA-DR13 (13,9%) [45]. В другом исследовании из этой же страны у кандидатов на трансплантацию почки наиболее часто выявлялись HLA-А02, HLA-B35 и HLA-DR11, что также созвучно с нашими результатами (у нас данные АГ выявлялись в 53,7%, 19,75% и 16,05% случаев соответственно) [44].…”
Section: Discussionunclassified
“…The most common allelic groups for each locus were HLA‐A*02 (25.4%), HLA‐B*44 (10.9%), and HLA‐DRB1*13 (13.9%), and the most common haplotypes were HLA‐A*01 ~ B*08 ~ DRB1*03 (2.3%), A*02~B*44~DRB1*07 (1.2%), and A*03 ~ B*07 ~DRB1*11 (1.0%). Significant differences in allele frequencies were observed among population groups based on skin color for the following allelic groups HLA‐A*68 , ‐B*08 , and ‐B*58 . Similarly, Ravazzi‐Gauch et al described the frequencies for 2624 renal transplant patients, all from São Paulo state.…”
Section: Transplant and Disease Association Studiesmentioning
confidence: 98%
“…In this study, associations were found between the allelic groups HLA-A*78 and HLA-DRB1*11 with end-stage renal disease 53 (Table 2). Saito et al 60 described the allelic and haplotypic frequency in 512 patients (319 White, 134 Brown, and 69 Black), also in chronic renal failure candidates for renal transplantation, all from the Northern and Northwest regions of Paraná state. The most common allelic groups for each locus were HLA-A*02 (25.4%), HLA-B*44 (10.9%), and HLA-DRB1*13 (13.9%), and the most common haplotypes were HLA-A*01~B*08~DRB1*03 (2.3%), A*02~B*44D RB1*07 (1.2%), and A*03~B*07~DRB1*11 (1.0%).…”
Section: Transplant and Disease Association Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A DRC apresenta altas taxas de incidência e prevalência e tem se configurado como um problema de saúde mundial, com elevados custos para a saúde pública, sendo o transplante renal considerado uma das melhores opções de terapia e reabilitação de pacientes com doença renal em estágio terminal (14,15,16).…”
Section: Introductionunclassified